MENYALAHKAN KORBAN DALAM KASUS PELECEHAN SEKSUAL: PERSPEKTIF HUKUM DAN DAMPAKNYA TERHADAP PERLINDUNGAN KORBAN - Lutfi Ramadhani Tiara Putri (Jurnal Ilmiah Advokasi, 2025)
The phenomenon of Blaming the victim in sexual abuse cases is prevalent in both the legal system and society, where victims are often blamed, worsening their psychological condition and hindering their access to justice. This study explores the Indonesian legal perspective on handling sexual harassment cases involving victim blaming and its impact on victim protection. Using a normative juridical approach, it analyzes Law Number 12 of 2022 on Criminal Acts of Sexual Violence (UU TPKS), which aims to protect victims' rights and prevent discrimination and stigma. The findings reveal that despite the protections provided by the TPKS Law, victim blaming still occurs during legal processes, exacerbating trauma and obstructing the pursuit of justice. Therefore, the study emphasizes the need for better understanding and training for law enforcement officials, along with socializing to the public to reduce stigma and improve legal protection for victims of sexual abuse.Keywords: Blaming the Victim; Sexual Abuse; Legal Perspective; Victim Protection; Social Stigma